(untitled) - Dacey, John S. (Boston, MA., 2004)
"Human Development Across the Lifespan, 5e" by Professors John Dacey and John Tavers, provides a well balanced, chronological view of the lifespan from conception through death. The authors effectively utilize their wealth of experience to lead students to an understanding of the interplay of biological, sociological and psychological forces in human development. As in previous editions, the 5th edition of "Human Development Across the Lifespan" reflects the authors exhaustive research and careful application of relevant theories in a thorough, yet engaging presentation. New and updated content, contemporary applications and a more concise format place theories and concepts in a context that is meaningful to students from a variety of disciplines including: psychology, education, nursing, home economics, and developmental psychology.
Keywords: Developmental psychology,Tâm lý học phát triển